Hearing of the Child in Family Law Cases - Limantė, Agnė; Račkauskaitė-Burneikienė, Aistė (Teisė, 2018)
The article analyses the duty of hearing of the child in parental responsibility cases. It firstly discusses the international, regional and national instruments establishing such duty upon the courts. Then it seeks to define the duty of hearing of the child and its limits. Particular attention is paid to the different practice of states when implementing this child’s right in practice.